Design and bulletproof performance investigation on the ceramic/metal laminated composite. (20th August 2020) - Li, Bianhong; Deng, Hongbin; Gao, Xiangsheng; Gao, Hanjun
In the current study, seven types of laminated composites are designed to replace the existing 616 steel plate with 5 mm thickness for the bulletproof. An explicit dynamic finite element model is developed to simulate the bullet penetration process using ANSYS Workbench software. And a specific bulletproof coefficient, which considers the ultimate bulletproof speed and area density of the target plate, is proposed and calculated, and the overall bulletproof performances of the composites and 616 steel plate are compared. The specific bulletproof coefficients of seven composites are increased by 12.53%, 14.77%, 13.28%, 12.20%, 19.59%, 23.81%, and 20.67%, respectively. The type F is the optimal type among all the structures. Eventually, the optimal composites are validated under different bullet hit positions and double-bullet situations. Results show that all the seven composites and 616 steel with 5 mm thickness can effectively defend 5.62 mm bullets, and no damage or failure is observed. Although the impact stiffness and ultimate bulletproof speed are both decreased, the area density and density are also significantly decreased.